Electromechanobiology of Cartilage and Osteoarthritis A Tribute to Alan Grodzinsky on his 75th Birthday - Connizzo, Brianne K.; Han, Lin; Sah, Robert L. (Advances in Experimental Medicine and Biology, 2023)
This is an open access book. In honor of his 75th birthday, we reflect on the impact of the pioneering work of Alan Grodzinsky and his laboratory. This volume includes in-depth discussions of tissue electromechanics, mechanobiology and biomechanics, and matrix biology in addition to the latest advancements in understanding the pathogenesis, progression and treatment of osteoarthritis. Unique to this volume, we overview decades of groundbreaking research that set the stage for the latest efforts in the field, highlighting the legacy of one researcher and their trainees.